Exploring swift heavy ion-induced perpendicular magnetic anisotropy and tunnel magnetoresistance in CoFe2O4/MgO/ZnFe2O4 multilayers: X-ray magnetic circular dichroism study - Ritika Charak; Sanjeev Gautam; Shaffy Garg; Pardeep K. Thakur; Navdeep Goyal; Younghak Kim; Keun Hwa Chae (AIP Advances)
Magnetic tunnel junctions (MTJs), consisting of two ferromagnetic electrodes separated by an insulating layer, have been foundational in spintronics. This study expands the traditional MTJ framework by incorporating an antiferromagnetic electrode alongside a ferromagnetic one to elucidate the interplay between perpendicular magnetic anisotropy (PMA) and tunnel magnetoresistance (TMR). Specifically, we investigate the relationship among spin-orbital magnetic moments, PMA, and TMR in pristine and Ag-irradiated (200 MeV) thin films of CoFe2O4 (40 nm)/MgO (20 nm)/ZnFe2O4 (40 nm). Angle-dependent soft X-ray magnetic circular dichroism (XMCD), together with element-specific hysteresis loops at the Fe L-edge, reveals that both the pristine and swift heavy ion (SHI)-multilayer stacks display magnetic anisotropy, characterized by a decreased XMCD intensity from out-of-plane (perpendicular) to in-plane (parallel) geometry. This reduction in the XMCD intensity correlates with spin polarization, establishing a direct relationship with the TMR of the MTJ. Furthermore, the analysis confirms that TMR decreases as the measurement angle decreases. Therefore, this investigation underscores the pivotal role of spin-orbital magnetic moments in influencing the PMA and TMR properties of CoFe2O4/MgO/ZnFe2O4 MTJs.